Effect of Groundnut Pod Condition on the Microbial Content and Aflatoxin Contamination in the Groundnut Seeds - Magzoub, Reem, A. M. A.; Yasin, Atif, A. A.; Abdel-Rahim, Awad, A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study was investigated the effect of groundnut pod condition on the microbial content and aflatoxin contamination in the groundnut seeds in Sudan, which collected from irrigated area (Gezira) and rain-fed area (Al-fao and Kordofan). The samples were investigated for their fungal growth using potato dextrose agar (PDA) media and for their aflatoxin contamination using thin layer chromatography (TLC) technique. High percentage of the groundnut seeds were found unshelled sound intact (53.33-63.00%), while the low percentage was unshelled shrink/damaged (10.33-19.34%). The infection by A. flavus and aflatoxins contamination were found to be high in the split samples either shelled or unshelled which collected from Gezira area (56.67%), whereas, the low percentage was (10.00%) in the unshelled shrink/damaged samples which collected from Kordofan area. Microbial content showed that the sound intact seeds either shelled or unshelled were free from A. flavus and aflatoxins, while the split and shrink/damaged samples either shelled or unshelled were infected by A. flavus and contaminated by aflatoxins. Moreover, High percentage of fungs infection other than A. flavus were obtained (40.00-43.33%) in split and shrink/damaged shelled samples, however, low percentage were obtained (10.00%) in intact samples either shelled or unshelled which collected from Gezira area